2001
DOI: 10.1007/s002160101054
|View full text |Cite
|
Sign up to set email alerts
|

Hyphenation of a near-infrared Echelle spectrometer to a microplasma for element-selective detection in gas chromatography

Abstract: The coupling of a near-infrared Echelle spectrometer (NIRES) with a gas chromatograph for element-selective detection is introduced. The miniaturized capacitive plasma device is operated at a frequency of 40.68 MHz and is mounted directly on an Hewlett-Packard HP6890 GC. First results with a mixture of halogenated standard compounds are presented and discussed in terms of the advantages and problems with this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Changes in the spectral emission patterns and the intensities of analyte lines were used to detect H 2 , O 2 , N 2 , CO 2 , and Ar. A similar 40.68-MHz miniaturized capacitive plasma device coupled to a GC was reported by Cziesla et al (50), which was distinguished from previous systems by its extremely simple construction and high robustness. A plasma with a diameter of 140 μm was coupled to a near-infrared echelle spectrometer, which was designed to detect various nonmetals in the near-infrared spectral range, especially the halogens and sulfur.…”
Section: Microplasma Detectors Based On Optical Emission Spectrometrysupporting
confidence: 53%
“…Changes in the spectral emission patterns and the intensities of analyte lines were used to detect H 2 , O 2 , N 2 , CO 2 , and Ar. A similar 40.68-MHz miniaturized capacitive plasma device coupled to a GC was reported by Cziesla et al (50), which was distinguished from previous systems by its extremely simple construction and high robustness. A plasma with a diameter of 140 μm was coupled to a near-infrared echelle spectrometer, which was designed to detect various nonmetals in the near-infrared spectral range, especially the halogens and sulfur.…”
Section: Microplasma Detectors Based On Optical Emission Spectrometrysupporting
confidence: 53%
“…For this purpose, optical emission spectroscopy (OES) is combined with chromatography, in which a small amount of a liquid sample transferred by the electrophoresis effect in a capillary is taken into a micoplasma source, and the emission spectrum is analyzed for chemical constituents. In earlier days, a DC-discharge source with inner electrodes was used [52], but later ICP-type, coaxial type and microstrip-line type sources driven by high frequency power sources in a wide frequency range from RF to microwave have come to be used [53][54][55][56]. A micro-HC type DC source is also going to be used owing to its high plasma density [37,57].…”
Section: Applications To Micro Chemical Analysesmentioning
confidence: 99%
“…2224 As a group, sensitivity was often tested using one gas or a similar series of halogen-containing hydrocarbons as the spectral lines for F, Cl, and Br are readily distinguished and spectrally remote. 20,24,25 Yet some studies have demonstrated detection of a series within the same family of compounds, e.g., alcohols. 23,26 Uniformly these plasmas have operated within an inert carrier gas.…”
Section: Introductionmentioning
confidence: 99%